СИСТЕМНО-СИНЕРГЕТИЧНІ ОСОБЛИВОСТІ ОРКЕСТРОВО- АНСАМБЛЕВОЇ ПІДГОТОВКИ МАЙБУТНЬОГО ВЧИТЕЛЯ МУЗИКИ - Plyachenko, Tatiana (Continuing Professional Education: Theory and Practice, 2019)
In the article „System-synergetics features of orchestral-band preparation of future music master” the specifi c of organization of the orchestral-band teaching of future music master is exposed on synergetics bases, principles of approaches of the systems and synergetics, the observance of which is provided by success of orchestral-band preparation of students, are certain.